Bonsoir,
f(x) ≤ 6
-3x(x + 4) ≤ 6
-3x² - 12x ≤ 6
-3x² - 12x - 6 ≤ 0
3x² + 12x + 6 ≥ 0
x² + 4x + 2 ≥ 0
x² + 4x + 4 - 4 + 2 ≥ 0
(x² + 4x + 4) - 4 + 2 ≥ 0
(x + 2)² - 2 ≥ 0
(x + 2)² - (√2)² ≥ 0
(x + 2 + √2)(x + 2 - √2) ≥ 0
Racines : x + 2 + √2 = 0 ==> x = -2 - √2
x + 2 - √2 = 0 ==> x = -2 + √2
[tex]\begin{array}{|c|ccccccc|}x&-\infty&&-2-\sqrt{2}&&-2+\sqrt{2}&&+\infty \\ x+2+\sqrt{2}&&-&0&+&+&+&\\ x+2-\sqrt{2}&&-&-&-&0&+&\\ Produit&&+&0&-&0&+&\\ \end{array}\\\\\\S=]-\infty;-2-\sqrt{2}]\ \cup\ [-2+\sqrt{2};+\infty[[/tex]